Les collections composites du musée de la Chasse et de la Nature - Marie-Christine Prestat (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Derived from a private collection, the musée de la Chasse et de la Nature was conceived in the sixteen as a fine art, technique and natural history museum. Since 2007, a new museography has opened the collection to contemporary art. The juxtaposition of taxidermies, paintings, arms and others objects allows us to approach the problems of conservation and the issues involved in exhibitions.